IMPLEMENTASI UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN KAJIAN KHUSUS HAK PEJALAN KAKI PERSPEKTIF HUKUM ISLAM - Zetrie Andeka Muslimah (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2018)
Abstract: It is known that Law Number 22 Year 2009 concerning Road Traffic and Transportation in the City of Bengkulu has not been implemented properly. Then, the application of Law Number 22 Year 2009 in Article 28 Paragraph 2 has not been properly implemented so that pedestrian rights have not been maximally given, and furthermore Law Number 22 Year 2009 concerning Road Traffic and Transport has been made in accordance with Islamic law where the manufacture is intended for the benefit of the people.Keywords: Pedestrians, Law Number 22 of 2009, benefit of the people, Islamic law